The Effect Of Using ICT Based Graphic Organizer Across The Students’ Difference Level of Writing Ability - Sabarun Sabarun (Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi, 2017)
The study is aimed at investigating whether ICT based graphic organizer gives facilitative effect or not across the students’ difference level of writing ability. The study belongs to quasi experimental study by applying counterbalance procedure to collect the data. The participants are the 26 students of English department of Palangka Raya State Islamic Institute of 2017/ 2018 academic year. To test the hypotheses, a one way ANOVA test was applied. The research findings shows that, the data fulfills the normality using Shapiro Wilk test (p= 0.420, 0.046, 0.50, and 0.638> 0.05) and homogeneity of variance using Levene’s test (p= 0.541> 0.05). It is found that the F value is45.050, with the significance (p= 0.050> 0.000). Therefore, F table 4.040<45.050>3.190at the 5% and 1% of significant level (Df= 48). It meant that there is a very statistically significant difference on students’ writing achievement both for the bright and poor students between the students who writean expository essay using ICT Based graphic organizer and those who write an expository essay without using ICT Based graphic organizer